(untitled) (Multidisciplinary Journal of Science and Technology, 2025)
In this article in raising children aged children coperation of educators with parents, modrn trends and best practices are analyzed, In order to develop children’s allround development, the importance of educational institutions with families is expressed, Currently, effective communication with parents based on modern approaches is an interactive method, it is clear that the importance of use of family class programs and innovation. At the same time, the advanced methoods of working with parents and ways to apply to practice.